SYAIR BRAMA SAHDAN: KAJIAN SEMOTIK RIFFATERRE (BRAMA SAHDAN'S POETRY: RIFFATERRE'S SEMIOTIC STUDY) - Raudatul Munawwarah (Universitas Lambung Mangkurat, 2023)
Â AbstractBrama Sahdan's Poetry: Riffaterre's Semiotic Study. Brama Sahdan's poetry is poetry in the collection of the Lambung Mangkurat Museum, which is important to study, considering the need for more knowledge about the meanings contained in the text of Brama Sahdan's poetry. However, through Riffaterre's semiotic approach, the meaning of the symbols contained in the text can be known. Based on this background, this research aims to identify (1) the meaning contained in Syair Brama Sahdan based on heuristic and hermeneutic readings; (2) the matrix, models, and variants in Brama Sahdan's poetry. The method used in this study is a descriptive research method with a qualitative approach, where the type of research is classical written literature with a semiotic approach to Riffaterre's theory. The results of the study show that the meaning contained in Syair Brama Sahdan implies that a king is a person who has the characteristics: power, supernatural powers, warriors (never give up), and wisdom; women are interpreted as valuable figures that must be fought for even though through war; war is interpreted as an activity to gain power but still pay attention to the prevailing customary rules; and customs in royal marriages which are interpreted as mandatory rituals carried out in welcoming the joining of the two new kingdoms. The matrix in Brama Sahdan's poetry is a description of the life journey of a great king. This poetry matrix is transformed into the Brama Sahdan model. The model is then converted into six variants in the poem's verses.Keywords: poetry, semiotic, riffaterreAbstrakSyair Brama Sahdan: Kajian Semiotik Riffaterre. Syair Brama Sahdan merupakan syair koleksi Museum Lambung Mangkurat yang penting untuk dikaji mengingat masih minimnya pengetahuan mengenai makna-makna yang terdapat dalam naskah Syair Brama Sahdan. Melalui pendekatan semiotik Riffaterre, dapat diketahui makna dari simbol-simbol yang terdapat dalam naskah. Berdasarkan latar belakang tersebut, maka tujuan penelitian ini yaitu untuk mengidentifikasi (1) makna yang terdapat dalam Syair Brama Sahdan berdasarkan pembacaan heuristik dan hermeneutik; (2) matriks, model, dan varian dalam syair Brama Sahdan. Metode yang digunakan dalam penelitian ini adalah metode penelitian deksriptif dengan pendekatan kualitatif dan jenis penelitiannya adalah sastra tulis klasik dengan pendekatan semiotika teori Riffaterre. Berdasarkan pembacaan heuristik dan hermeneutik, hasil penelitian menunjukkan bahwa makna yang terdapat dalam Syair Brama Sahdan mengandung makna bahwa raja sebagai orang yang memiliki sifat kekuasaan, kesaktian, keprajuritan (pantang menyerah), dan kebijaksanaan; perempuan dimaknai sebagai sosok berharga yang harus diperjuangkan meskipun melalui peperangan; perang dimaknai sebagai suatu aktivitas untuk mendapatkan kekuasaan namun tetap memperhatikan aturan adat istiadat yang berlaku; dan adat istiadat dalam pernikahan raja yang dimaknai sebagai ritual wajib yang dilaksanakan dalam menyambut bergabungnya dua kerajaan baru. Matriks dalam syair Brama Sahdan merupakan gambaran perjalanan hidup seorang raja besar. Matriks syair ini ditransformasikan menjadi model Brama Sahdan. Model tersebut kemudian ditransformasikan menjadi enam varian yang terdapat dalam bait-bait syair.Kata Kunci: syair, semiotik, riffaterre